ANALYSIS OF THE 2025 EDUCATION REPORT OF ACEH PROVINCE AND ITS IMPLICATIONS FOR SCIENCE EDUCATION (PHYSICS AND BIOLOGY) - Adawiyah, Rabiyatul (Prodi Tadris Biologi Fakultas Agama Islam Universitas Muhammadiyah Aceh, 2025)
This study aims to analyze the achievements of literacy, numeracy, and character education in Aceh Province based on the 2025 Education Report, as well as to examine their implications for science education, particularly Physics and Biology. The research data were obtained from the Aceh Education Quality Assurance Agency (BPMP) through the Education Report dashboard. The results show that literacy achievement reached 67.61, numeracy 66.61, and character 58.12. Of the 504 schools analyzed, 261 schools (51.8%) were categorized as good, 170 schools (33.7%) as fair, and 73 schools (14.5%) as poor. The 2023–2025 trend indicates an increase in literacy and numeracy achievement, while character achievement remained relatively stagnant. In the context of science learning, these findings highlight the need to strengthen scientific literacy, experiment-based numeracy, and the development of scientific attitudes through contextual learning and ethno-STEM approaches. The integration of the Independent Curriculum (Kurikulum Merdeka) with a deep learning approach offers a solution to reinforce literacy, numeracy, and character simultaneously within the context of science education.